Differential impact of divalent metals on native elongating transcript sequencing (NET-seq) protocols for RNA polymerases I and II - Abigail K. Huffines; David A. Schneider (PLoS ONE, 2025)
Throughout all domains of life, RNA polymerases (Pols) synthesize RNA from DNA templates, a process called transcription. During transcription, Pols require divalent metal cations for nucleotide addition and cleavage of the nascent RNA after misincorporation or polymerase stalling. Recently, several next-generation sequencing techniques have emerged to study transcription at single-nucleotide resolution in vivo. One such technique, native elongating transcript sequencing (NET-seq), allows for isolation of transcription elongation complexes associated with a specific Pol, defining polymerase occupancy on the DNA template. Originally developed to study RNA polymerase II (Pol II), NET-seq has been adapted for RNA polymerase I (Pol I) and bacterial RNA polymerase. We recently optimized Pol I NET-seq in Saccharomyces cerevisiae, however, we omitted nucleases and their metal cofactors, which are commonly used in Pol II NET-seq. Here, we investigated the effect of CaCl2 ± MNase and MnCl2 ± DNase I on Pol I occupancy. We found that exposure of Pol I to CaCl2 and MnCl2 during NET-seq caused a significant reduction in immunoprecipitation of nascent rRNA compared to the untreated control samples, with a more severe effect when incubated with MnCl2 vs. CaCl2. Surprisingly, in contrast to the Pol I results, we found that metal treatment during Pol II NET-seq did not have a significant effect on nascent transcript capture. Taken together, these observations reinforce the conclusion that transcription elongation complexes formed by Pols I and II have unique characteristics and emphasize the need to carefully consider experimental conditions deployed in all stages of nucleic acid library generation.